Meningkatkan Hasil Belajar dan Kemandirian Peserta Didik dengan Model PBL Berbantuan Media Audiovisual Materi "Manusia Sebagai Citra Allah" Kelas VII Fase D SMPN 1 Mempawah Hulu - C.F. Yakub; Mawarni Gea; Agustinus Mulyono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research was conducted based on the low quality of the process and learning outcomes in Catholic Religious Education subjects at SMP Negeri 1 Mempawah Hulu. This study aims to improve learning outcomes and student independence in Catholic Religious Education learning, especially in the material of Man as the Image of God in class VII Phase D of SMPN 1 Mempawah Hulu. The application of the Problem Based Learning (PBL) learning model can explore the effectiveness and quality of learning with indicators of improving student learning outcomes in the Cognitive and affective aspects. In the affective aspect, the researcher developed an independent dimension in the Pancasila Student Profile. Using a quantitative approach, this study involved 31 students in class VII D. The study was conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. Data were collected based on the results of learning tests and observations of attitudes in the learning process in cycles 1 and 2. The results showed an increase in the average score in the cognitive aspect, namely from 73.3 in cycle 1 to 85.6 in cycle 2 or an increase of 16.7%. In the affective aspect, namely by observing learning independence, data was obtained that the average score of the affective aspect in cycle 1 was 80, increasing to 86 in cycle 2 or an increase of 7.5%. In addition, student independence in the learning process also increased, as indicated by their ability to solve problems independently and work collaboratively. The increase in learning outcomes can be seen from the average score of students which increased from the first cycle to the second cycle. Likewise, the level of student independence increased based on the results of the questionnaire and observations. Based on these findings, it can be concluded that the PBL learning model assisted by audio-visual media is effectively able to improve learning outcomes and student learning independence in Catholic Religious Education material.